Specific management of hemorrhagic stroke: Guidelines of Turkish Society of Cerebrovascular Diseases 2015 [Özel hemorajik inme tedavisi: Türk Beyin Damar Hastaliklari Dernegi inme tani ve tedavi kilavuzu 2015] - (:unkn) unknown (Turkish Society of Cerebrovascular Diseases, 2015)
In this section, latest developments about special hemorrhagic stroke treatments including medical and interventional treatment were updated and presented based on recent evidences.
Keywords: Hemorrhagic stroke; Interventional treatment; Medical treatment